초경량 실리카 에어로젤 초단열재의 현황 및 전망 - 서동진(Dong Jin Suh) (청정기술, 2022)
Since nanoporous silica aerogel was first synthesized in 1931, its potential as an ultra-lightweight superinsulation material has been steadily attracting attention. Silica aerogel is the best thermal insulation material to date. However, the potential applications of this lightweight material have so far been hindered by its inherent fragibility and brittleness arising from its ultra-porous nature. Although the monolithic form of silica aerogel has the best ultra-lightweight superinsulation properties, it cannot be used in this form. Instead it is used in the form of powders, particles, and blankets. However, these forms still have shortcomings. Silica aerogel is most widely applied in the form of a fiber-reinforced aerogel blanket, but this form is likely to generate dust when handled. Although silica aerogel particles have been proven to be non-toxic to humans, dust formation remains a major barrier to the widespread application of silica aerogel blankets. This paper will investigate the unique properties of silica aerogel and determine what fields it can be used in or potentially be used in due to its unique properties. In addition, we will review the important advances in silica aerogel synthesis technology and its commercialization so far, and then consider the problems that exist for its widespread commercialization in the future and how to overcome them. 나노다공성 실리카 에어로젤은 1931년 처음 합성된 이후 초경량 초단열재로서의 가능성이 꾸준히 주목받고 있다. 실리카 에어로젤은 현재까지 알려진 최고의 단열재이지만 소재 자체의 초다공성 특성으로 인해 본질적으로 피할 수 없는 부서지거나 깨지기 쉬운 성질 때문에 지금까지 실제 적용 가능성에는 한계가 있는 것도 사실이다. 단일체 형태의 실리카 에어로젤이 초경량 초단열 특성이 가장 우수하지만 그대로 사용할 수 없고 분말, 입자, 블랭킷 형태로 사용되고 있으며 그조차도 아직은 기대에 미치지 못하고 있다. 가장 널리 적용되는 형태의 실리카 에어로젤은 섬유에 담지시킨 에어로젤 블랭킷이지만 취급 시 먼지가 발생할 가능성이 있다. 실리카 에어로젤 입자가 인체에 독성이 없는 것으로 알려져 있지만 먼지 생성은 실리카 에어로젤 블랭킷의 광범위한 활용에는 가장 큰 장애요인으로 남아 있다. 본 논문에서는 실리카 에어로젤이 어떤 고유한 성질을 가지고 있는지, 그리고 그 고유한 성질을 이용하여 어떤 분야에 사용될 수 있거나 사용될 가능성이 있는지에 대해 살펴볼 것이다. 또한 지금까지의 중요한 합성 기술의 발전과 상용화가 진행되었던 과정을 살펴보고 향후 본격적인 상용화를 위해서는 어떤 문제점이 있고 그 극복 방안은 어떠한지 검토해 보고자 한다.